Hadith #2936 - Sunan Abi Dawud - Abdur Rahman bin Shmas'h عبد الرحمن بن شماسة; Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Ibn Ishaq محمد بن إسحاق بن يسار‎; Muhammad bin Salmah محمد بن سلمة بن عبد الله الباهلي; Uqba bin 'Amir al-Juhayni; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: The official who collects sadaqah (zakat) in a just manner is like him who fights in Allah’s path till he returns home.
Grade: Sahih